Optical measurements and mapping in Ga‐ and Al‐doped ZnO and Sn‐doped In2O3. Issue 7 (27th April 2015) - Look, D. C.; Leedy, K. D.
<x xml:space="preserve">Abstract</x> Hall‐effect/conductivity measurements in TCO materials such as Ga‐doped ZnO (GZO), Al‐doped ZnO (AZO), and Sn‐doped In2O3 (ITO) determine Hall mobility μH and sheet carrier concentration ns directly by measurements of current, voltage, and magnetic field. If thickness d is known, then ns can be converted into volume concentration n = ns/d. Optical measurements, on the other hand, determine analogous quantities μopt and nopt indirectly, usually by invoking the Drude model of the dielectric constant. Here we compare μopt and nopt obtained by Drude analysis of reflection, transmission, and spectroscopic‐ellipsometry (SE) measurements, with μH and n. Although reasonably good agreement between Hall effect and optical parameters can be obtained with all of these techniques, SE is especially attractive for non‐destructive, high‐density mapping of μ and n. Moreover, we can use degenerate scattering theory to convert maps of μ and n into maps of donor and acceptor concentration. This new mapping methodology is applied to GZO and ITO.